A case of postoperative spontaneous intussusception after laparoscopic low anterior resection for rectal cancer. Issue 1 (December 2016) - Kim, Young
Abstract Background Intussusception refers to a condition in which a segment of the intestine invaginates into the lumen of an adjacent segment of the intestine. Postoperative intussusception after gastrointestinal surgery is an uncommon clinical condition, and there is only one case report of small bowel intussusception after rectal cancer surgery. Here, we report a case of spontaneous small bowel intussusception following laparoscopic total mesorectal excision for rectal cancer. Case presentation A 56-year-old female military officer was referred to the Colorectal Surgical Department for mid-rectal cancer, 8 cm from the anal verge. The patient underwent laparoscopic low anterior resection and diverting loop ileostomy. On postoperative day 3, the patient complained of vomiting and abdominal pain, and a follow-up abdomino-pelvic computed tomography scan showed an ileo-ileal type intussusception. After two days of surgical observation, her clinical symptoms were not resolved. The patient underwent exploratory laparotomy. On exploration, intussusception was found 40 cm proximal to the loop ileostomy site. Segmental resection of the ileum was carried out, and there was no pathological leading point on the resected ileum. The patient was discharged on postoperative day 14 after the second operation and has remained in good health for two years. Conclusion We present a case of spontaneous small bowel intussusception after laparoscopic total mesorectal excision for rectal cancer that was treated by surgical resection 5 days after the index surgery.